Media Interaktif Manfaat Kesehatan Buah Mengkudu Pada Usia 18-29 Tahun Di Kota Palembang - Nanda Rahmadhani Syahputri; Mukhsin Patriansah; Bobby Halim (Penerbit dan Percetakan, CV. Picmotiv, 2024)
Noni fruit is known to have various important health benefits, but the main problem in this design is the lack of knowledge, understanding and public acceptance of noni fruit is still very low, especially among generation Z. This design adopts the design thinking method in developing media that can attract attention, increase interest, and encourage action and search for further information about noni fruit. The main objective of this design is to inform the young generation aged 18-29 years in the city of Palembang about the health benefits of noni fruit through an application as the main interactive media. The main media used is interactive media in the form of a special application to introduce the various benefits of noni fruit to the people of Palembang City. This application will be designed using an approach that is attractive and easy to understand by the younger generation, especially Gen-Z, which contains complete information about the health benefits of the fruit. noni which can be accessed or installed via a QR Code, by displaying illustrations of noni characters and displaying application features such as, kudu reminder, kudu kepo, noni content, kudu understand and there are other features which are explained in the design visualization section . In this way, it is hoped that it will help attract generation Z to try processed noni fruit in the city of Palembang.